Rare earth formate second-order nonlinear optical crystalline materials and their preparation and application
By developing second-order nonlinear optical crystalline materials of rare earth formate RE (HCOO)3 (RE = La or Gd), the problem that existing frequency multiplier crystals are difficult to meet the nonlinear optical requirements of different wavelength ranges is solved, and a strong powder frequency multiplication effect and a moderate birefringence are achieved, and its application in laser frequency conversion is expanded.
Patent Information
- Application Number
- CN202410298186.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-03-15
AI Technical Summary
The existing commercial frequency multiplier crystals are difficult to meet the nonlinear optical requirements of different wavelength ranges, and their shortcomings limit their practical application.
A second-order nonlinear optical crystalline material of rare earth formate RE(HCOO)3 (RE=La or Gd) was developed, and a material with a triangular pore structure was formed by combining rare earth metal cations and π-conjugated anion [HCOO]-, which enhanced the micropolarization rate and optical anisotropy.
The material exhibits strong powder frequency doubling effect (1.9×KDP and 2.0×KDP), moderate birefringence and large band gap. It is suitable for laser frequency conversion and other applications and has broad application prospects.
Smart Images

Figure CN118257002B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonlinear optical crystalline materials, and relates to a rare earth formate second-order nonlinear optical crystalline material and a preparation method and application thereof. Background Art
[0002] As a kind of optoelectronic functional material, nonlinear optical (NLO) crystalline materials are widely used in many fields such as laser frequency conversion, laser communication, optoelectronic modulation, laser ranging, medical treatment and national defense. With the development of society and the continuous expansion of application fields, the existing commercial frequency doubling crystals can hardly fully meet the needs of production and scientific research. The development of new NLO materials with better performance and suitable for different wavelength ranges is one of the important tasks and challenges faced by modern scientific researchers. At present, the use of π-conjugated planar triangular structural units (such as [BO3] 3- , [CO3] 2- , [NO3]-) is an effective strategy to develop new NLO materials, such as LiB3O5 (LBO), CsB3O5 (CBO), CsLiB6O 10 (CLBO), β-BaB2O4 (BBO) and KBe2BO3F2 (KBBF) crystals. However, the practical applications of these materials are limited by their inherent shortcomings. Therefore, the development of new high-performance NLO crystalline materials is an important research direction in the field of optoelectronic functional materials. Summary of the invention
[0003] The purpose of the present invention is to provide a rare earth formate RE (HCOO) 3 (RE = La or Gd) second-order nonlinear optical crystalline material and its preparation and application. The crystalline material has a planar triangular NLO functional unit, which is conducive to producing a large microscopic polarizability and a strong optical anisotropy, so that the material exhibits a strong powder frequency doubling effect (1.9×KDP and 2×KDP), a suitable birefringence (0.056@546nm and 0.052@546nm) and a large band gap (4.84eV and 4.78eV), etc.
[0004] The purpose of the present invention can be achieved by the following technical solutions:
[0005] One of the technical solutions of the present invention provides a rare earth formate second-order nonlinear optical crystalline material, whose chemical formula is RE(HCOO)3, wherein RE=La or Gd, and the crystalline material belongs to the trigonal system, the space group is R3m, and the unit cell parameters are α=β=90°, γ=120°, Z=3.
[0006] Furthermore, the chemical formula of the crystalline material is La(HCOO)3, which belongs to the trigonal system, the space group is R3m, and the unit cell parameters are α=β=90°,γ=120°,Z=3. Further preferably, the unit cell parameters are α=β=90°,γ=120°,Z=3. More preferably, the unit cell parameters are α=β=90°,γ=120°,Z=3. Most preferably, the unit cell parameters are α=β=90°, γ=120°, Z=3.
[0007] The crystal structure of the organic-inorganic hybrid crystalline material La(HCOO)3 of the present invention is as follows Figure 2 As shown. Each La atom is coordinated with nine oxygen atoms to form a [LaO9] polyhedron. Each [LaO9] polyhedron and the adjacent nine [HCOO] - The groups form a three-dimensional framework through corner-sharing connections, presenting a through-type triangular channel structure parallel to the c-axis on the ab plane. This structural configuration enhances the structural stability of the crystal.
[0008] Furthermore, the chemical formula of the crystalline material is Gd(HCOO)3, which belongs to the trigonal system, the space group is R3m, and the unit cell parameters are α=β=90°,γ=120°,Z=3. Further preferably, the unit cell parameters are α=β=90°,γ=120°,Z=3. More preferably, the unit cell parameters are α=β=90°,γ=120°,Z=3. Most preferably, the unit cell parameters are α=β=90°, γ=120°, Z=3.
[0009] The crystal structure of the organic-inorganic hybrid crystalline material Gd(HCOO)3 of the present invention is as follows Figure 2 As shown. Each Gd atom is coordinated with nine oxygen atoms to form a [GdO9] polyhedron. Each [GdO9] polyhedron and the nine adjacent [HCOO] - The groups form a three-dimensional framework through corner-sharing connections, presenting a through-type triangular channel structure parallel to the c-axis on the ab plane. This structural configuration enhances the structural stability of the crystal.
[0010] The second technical solution of the present invention provides a method for preparing a rare earth formate second-order nonlinear optical crystalline material. First, a rare earth source, a formic acid source, a mineralizer and a mixed solvent are mixed and added to a reaction container. After heating for reaction, the mixture is cooled to room temperature to obtain a colorless and transparent crystal, which is the target product.
[0011] Furthermore, the added amounts of the rare earth source, formic acid source and mineralizer satisfy the following conditions: the molar ratio of the rare earth element, formic acid source and mineralizer is (1-10):(1-10):(0.5-1), preferably (1-10):(1-10):(0.5-0.8).
[0012] Furthermore, the rare earth source is a nitrate containing a rare earth element (La and / or Gd).
[0013] Furthermore, the formic acid source is anhydrous oxalic acid.
[0014] Furthermore, the mineralizer is sodium carbonate.
[0015] Furthermore, the mixed solvent is a solution of DMF and water in a volume ratio of (1-3):(1-3). More preferably, the volume ratio of DMF and water is (2-3):(1-2).
[0016] Furthermore, the heating reaction temperature is 120-150° C. and the time is not less than 70 hours.
[0017] The third technical solution of the present invention provides the application of rare earth formate second-order nonlinear optical crystalline materials in laser frequency converters, optical parametric oscillators, optical parametric amplifiers and photoelectric rectifiers.
[0018] Furthermore, the material is used in a laser frequency converter and outputs 532nm laser under 1064nm laser irradiation.
[0019] Specifically, La(HCOO)3 crystal, as a second-order nonlinear optical crystalline material, outputs a strong 532nm laser under 1064nm laser irradiation. Its powder double frequency intensity is 1.9 times that of KDP crystal, and phase matching can be achieved.
[0020] Specifically, Gd(HCOO)3 crystal, as a second-order nonlinear optical crystalline material, outputs a strong 532nm laser under 1064nm laser irradiation, and its powder frequency doubling intensity is 2.0 times that of KDP crystal, and phase matching can be achieved.
[0021] The present invention combines rare earth metal cations and π conjugated anions [HCOO] -Combined with the above, a rare earth formate second-order nonlinear optical crystal RE(HCOO)3 (RE=La or Gd) with a triangular pore structure was discovered. The crystalline material has a planar triangular NLO functional unit, which is conducive to the generation of large microscopic polarizability and strong optical anisotropy, which makes the material show a strong powder frequency doubling effect (1.9×KDP and 2.0×KDP), moderate birefringence (0.056@546nm and 0.052@546nm) and a large band gap (4.84eV and 4.78eV).
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] (1) The present application provides a new second-order nonlinear optical crystal La(HCOO)3. The crystalline material has a large frequency doubling effect. The frequency doubling intensity under 1064nm laser irradiation is 1.9 times that of KDP crystal, and phase matching can be achieved. In addition, the band gap of the crystalline material is 4.84eV, the birefringence is 0.056@546nm, and the thermal decomposition temperature is 380℃. The crystalline material has broad application prospects in the field of nonlinear optics.
[0024] (2) The present application also provides a method for preparing the second-order nonlinear optical crystal La(HCOO)3, and a colorless La(HCOO)3 crystal is prepared by a solvothermal method. The synthesis method is simple, the synthesis conditions are mild, and it is easy to obtain a high-purity millimeter-level single crystal.
[0025] (3) The present application provides a new second-order nonlinear optical crystal Gd(HCOO)3. The crystalline material has a large frequency doubling effect. The frequency doubling intensity under 1064nm laser irradiation is 2.0 times that of KDP crystal, and phase matching can be achieved. In addition, the band gap of the crystalline material is 4.78eV, the birefringence is 0.052@546nm, and the thermal decomposition temperature is 380℃. The crystalline material has broad application prospects in the field of nonlinear optics.
[0026] (4) The present application also provides a method for preparing the second-order nonlinear optical crystal Gd(HCOO)3, and a colorless Gd(HCOO)3 crystal is prepared by a solvothermal method. The synthesis method is simple, the synthesis conditions are mild, and it is easy to obtain a high-purity millimeter-level single crystal. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the crystal structure of La(HCOO)3;
[0028] Figure 2 It is a schematic diagram of the crystal structure of Gd(HCOO)3;
[0029] Figure 3The X-ray diffraction pattern of sample 1-1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the pattern obtained by X-ray diffraction test after sample 1-1# is ground into powder;
[0030] Figure 4 The X-ray diffraction pattern of sample 2-1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the pattern obtained by X-ray diffraction test after sample 2-1# is ground into powder;
[0031] Figure 5 is the UV-Vis-NIR absorption spectrum of sample 1-1#;
[0032] Figure 6 is the UV-Vis-NIR absorption spectrum of sample 2-1#;
[0033] Figure 7 is the infrared spectrum of sample 1-1#;
[0034] Figure 8 is the infrared spectrum of sample 2-1#;
[0035] Fig. 9 This is the thermogravimetric analysis spectrum of sample 1-1#;
[0036] Fig.10 This is the thermogravimetric analysis spectrum of sample 2-1#;
[0037] Fig.11 It is the second harmonic signal diagram of sample 1-1# and standard KDP sample with sample size ranging from 105 to 150 μm;
[0038] Fig.12 This is the second harmonic phase matching diagram of sample 1-1# in the 1064nm band;
[0039] Fig.13 It is the second harmonic signal diagram of sample 2-1# and standard KDP sample with sample size ranging from 105 to 150 μm;
[0040] Fig.14 This is the second harmonic phase matching diagram of sample 2-1# in the 1064nm band. DETAILED DESCRIPTION
[0041] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0042] Example:
[0043] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0044] Embodiment 1:
[0045] Preparation of samples 1# to 8#
[0046] The rare earth lanthanum source, formic acid source, mineralizer and mixed solvent are mixed, added into a polytetrafluoroethylene-lined autoclave, heated in an oven and then cooled to room temperature to obtain colorless and transparent La(HCOO)3 crystals.
[0047] The relationship between the type and ratio of raw materials in the initial mixture, the constant temperature, the constant temperature time and the sample number is shown in Table 1.
[0048] Table 1 Correspondence between samples, raw materials and synthesis conditions
[0049]
[0050] Crystal structure analysis of samples 1-1# to 1-8#
[0051] The structures of samples 1-1# to 1-8# were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.
[0052] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 298.15K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the SHELXTL-97 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.
[0053] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 5 to 70°, and the scanning step is 0.02°.
[0054] Among them, the single crystal X-ray diffraction results show that samples 1-1#~1-8# have the same chemical formula and crystal structure, the chemical formula is La(HCOO)3, belongs to the trigonal system, the space group is R3m, and the unit cell parameters are α=β=90°, γ=120°, Z=3.
[0055] Take sample 1-1# as a typical representative, its crystal structure data is α=β=90°,γ=120°,Z=3. Its crystal structure is as follows Figure 1 shown.
[0056] The powder X-ray diffraction test results show that in the XRD spectra of samples 1-1# to 1-8#, the positions of the diffraction peaks of the samples and the diffraction peaks fitted by the single crystal data are the same, but the peak intensities are slightly different.
[0057] Take sample 1-1# as a typical example. Figure 3 As shown, the X-ray diffraction pattern obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is consistent with the peak position of the pattern obtained by X-ray diffraction test after sample 1-1# is ground into powder, indicating that the obtained sample has high purity.
[0058] UV-Vis-NIR absorption spectroscopy test
[0059] The diffuse reflectance absorption spectrum test of sample 1-1# was conducted on a Carry 5000 UV-visible-near infrared spectrophotometer from Agilent Technologies, USA. Figure 5 As shown by Figure 5 It can be seen that the band gap of this compound is 4.84 eV.
[0060] Infrared spectrum test
[0061] The infrared spectrum test of sample 1-1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 7 As shown, the characteristic absorption peaks in the infrared spectrum confirm that [HCOO] - The presence of groups.
[0062] Thermogravimetric testing
[0063] The thermogravimetric test of sample 1-1# was conducted on a Netzsch STA 409PC thermogravimetric analyzer manufactured by Netzsch Equipment Manufacturing Co., Ltd., Germany. The results are shown in the figure below. Fig. 9 As shown by Fig. 9 It can be seen that the compound can be stable to 380°C and has good thermal stability.
[0064] Frequency doubling test experiment and results
[0065] The frequency doubling test experiment of sample 1-1# is as follows: a Q-switched Nd:YAG solid laser is used to generate a laser with a wavelength of 1064nm and used as the fundamental frequency light to irradiate the tested crystal powder. The second harmonic generated is detected by a photomultiplier tube, and the second harmonic intensity is displayed by an oscilloscope. The crystal sample and the standard sample KDP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve, and the particle size ranges are 26-50, 50-74, 74-105, 105-150, 150-200, and 200-280μm. Observe the change law of the frequency doubling signal with the particle size to determine whether it can achieve phase matching. Under the same test conditions, compare the second harmonic intensity generated by the sample and the standard sample KDP to obtain the relative size of the sample frequency doubling effect.
[0066] The test results show that the compound La(HCOO)3 has a large powder frequency-doubled effect. Under 1064nm wavelength laser irradiation, the frequency-doubled signal intensity is 1.9 times that of KDP crystal (such as Fig.11 ). The crystalline material can achieve phase matching under 1064nm laser irradiation (such as Fig.12 ).
[0067] Example 2
[0068] Preparation of samples 1# to 8#
[0069] The rare earth gadolinium source, formic acid source, mineralizer and mixed solvent are mixed, added into a polytetrafluoroethylene-lined autoclave, heated in an oven and then cooled to room temperature to obtain colorless and transparent Gd(HCOO)3 crystals.
[0070] The relationship between the type and ratio of raw materials in the initial mixture, the constant temperature, the constant temperature time and the sample number is shown in Table 2.
[0071] Table 2 Correspondence between samples and raw materials and synthesis conditions
[0072]
[0073]
[0074] Crystal structure analysis of samples 2-1# to 2-8#
[0075] The structures of samples 2-1# to 2-8# were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.
[0076] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 298.15K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the SHELXTL-97 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.
[0077] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 5 to 70°, and the scanning step is 0.02°.
[0078] Among them, the single crystal X-ray diffraction results show that samples 2-1#~2-8# have the same chemical formula and crystal structure, the chemical formula is Gd(HCOO)3, belongs to the trigonal system, the space group is R3m, and the unit cell parameters are α=β=90°, γ=120°, Z=3.
[0079] Take sample 2-1# as a typical example, its crystal structure data is α=β=90°,γ=120°,Z=3. Its crystal structure is as follows Figure 2 shown.
[0080] The powder X-ray diffraction test results show that in the XRD spectra of samples 2-1# to 2-8#, the positions of the diffraction peaks of the samples and the diffraction peaks fitted by the single crystal data are the same, but the peak intensities are slightly different.
[0081] Take sample 2-1# as a typical example. Figure 4 As shown, the X-ray diffraction pattern obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is consistent with the peak position of the pattern obtained by X-ray diffraction test after sample 2-1# is ground into powder, indicating that the obtained sample has high purity.
[0082] UV-Vis-NIR absorption spectroscopy test
[0083] The diffuse reflectance absorption spectrum test of sample 2-1# was conducted on a Carry 5000 UV-visible-near infrared spectrophotometer from Agilent Technologies, USA. Figure 6 As shown by Figure 6 It can be seen that the band gap of this compound is 4.78 eV.
[0084] Infrared spectrum test
[0085] The infrared spectrum test of sample 2-1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 8 As shown, the characteristic absorption peaks in the infrared spectrum confirm that [HCOO] - The presence of groups.
[0086] Thermogravimetric testing
[0087] The thermogravimetric test of sample 2-1# was conducted on a Netzsch STA 409PC thermogravimetric analyzer manufactured by German Netzsch Equipment Manufacturing Co., Ltd. The results are shown in the figure below. Fig.10 As shown by Fig.10 It can be seen that the compound can be stable to 380°C and has good thermal stability.
[0088] Frequency doubling test experiment and results
[0089] The frequency doubling test experiment of sample 2-1# is as follows: a Q-switched Nd:YAG solid laser is used to generate a laser with a wavelength of 1064nm and used as the fundamental frequency light to irradiate the tested crystal powder. A photomultiplier tube is used to detect the generated second harmonic, and an oscilloscope is used to display the second harmonic intensity. The crystal sample and the standard sample KDP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve. The particle size ranges are 26-50, 50-74, 74-105, 105-150, 150-200, and 200-280μm. Observe the change law of the frequency doubling signal with the particle size to determine whether it can achieve phase matching. Under the same test conditions, the second harmonic intensity generated by the sample and the standard sample KDP is compared to obtain the relative size of the sample frequency doubling effect.
[0090] The test results show that the compound Gd(HCOO)3 has a large powder frequency-doubled effect. Under 1064nm wavelength laser irradiation, the frequency-doubled signal intensity is 2.0 times that of KDP crystal (such as Fig.13 ). The crystalline material can achieve phase matching under 1064nm laser irradiation (such as Fig.14 ).
[0091] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a rare earth formate second-order nonlinear optical crystalline material, characterized in that: The chemical formula of the crystalline material is RE(HCOO)3, wherein RE = La or Gd. The crystalline material belongs to the trigonal system and the space group is R 3 m , the unit cell parameters are a = 10.0~10.8 Å, b = 10.0~10.8 Å, c = 3.8~4.5 Å, α = β = 90°, γ = 120°, Z =3; The preparation method is specifically: First, a rare earth source, a formic acid source, a mineralizer and a mixed solvent are mixed, added to a reaction vessel, heated for reaction, and then cooled to room temperature to obtain a colorless and transparent crystal, which is the target product; The addition amounts of the rare earth source, formic acid source and mineralizer satisfy the following conditions: the molar ratio of the rare earth element, formic acid source and mineralizer is (1-10): (1-10): (0.5-1); The rare earth source is a nitrate containing the rare earth element La or Gd; The formic acid source is anhydrous oxalic acid; the mineralizer is sodium carbonate; The mixed solvent is a solution of DMF and water in a volume ratio of (1-3): (1-3); The heating temperature of the reaction is 120~150 ℃ and the time is not less than 70 h.
2. The method for preparing the rare earth formate second-order nonlinear optical crystalline material according to claim 1, characterized in that: The chemical formula of the crystalline material is La(HCOO)3, which belongs to the trigonal system and the space group is R 3 m , the unit cell parameter is a = 10.735~10.737 Å, b = 10.735~10.737 Å, c = 4.141~4.143 Å, α = β = 90°, γ = 120°, Z = 3; Or the chemical formula of the crystalline material is Gd(HCOO)3, which belongs to the trigonal system and the space group is R 3 m , the unit cell parameters are a =10.476~10.478 Å, b = 10.476~10.478 Å, c = 3.988~3.990 Å, α = β = 90°, γ = 120°, Z = 3.